Analytical and experimental data of liquid oxygen tank pressurisation system during stage hot test. (25th July 2020) - Xavier, M.; Edwin Raj, R.; Narayanan, V.
Highlights: System configuration of ground test stage and its hot test results. It is a theoretical analysis of LOX tank pressurization system of a cryogenic stage. It evaluates the performance of tank pressurization system during stage hot test. Test carried out to analyse diffusional evaporation of LOX into helium bubbles. Comparison of simulation results with stage hot test data. Abstract: A stage hot test was successfully conducted for qualifying the cryogenic stage designated as C25 for GSLV Mk III launch vehicle. Foam insulated liquid oxygen (LOX) tank of C25 stage was pressurized using helium gas to maintain tank pressure during engine operation. Helium gas admitted for tank pressurization caused heat transfer from ullage gas to cold tank wall, liquid free surface, tank internal elements, etc. Since time dependent heat loss from ullage gas column was one of the factors to be predicted for computing helium flow rate required during tank pressurisation, a simulation model representing heat transfer in ullage volume, tank geometry, liquid outflow, pressurant gas supply to ullage, gas supply through submerged bubbler, etc. was developed. In addition, to analyse the problem of lower evaporation rate of subcooled LOX caused by helium bubbling during stage hot test, separate helium bubbling test was carried out to understand the phenomenon of diffusion driven evaporation of subcooled LOX into helium bubbles. This model was updated with results of helium bubbling test carried out after stage hot test and the updated model results closely match with stage hot test data of liquid oxygen tank pressurization system of C25 cryogenic stage.